Erkenntnisgewinnung durch qualitative Methoden im Geographieunterricht – ein Vorschlag zur Kompetenzentwicklung am Beispiel subjektzentrierter Raumwahrnehmung - Thierer, Andreas (Zeitschrift für Geographiedidaktik (ZGD), 2011)
The integration of subject-oriented approaches to space in teaching geography makes it also necessary to reinforce the use of qualitative methods. This article illustrates the benefits of applying qualitative methods (biographical-narrative interviews, participant observation, mental maps). In the first part some relevant theoretical considerations about qualitative methods are outlined. This includes both a methodological framework and a structuring of competences within this specific field. The second part gives insights into how qualitative methods can be incorporated at school for research of subjective space perceptions.
Keywords: qualitative research, methodical competence, space perception, mental maps, school project